Teachers’ Beliefs on The Implementation of Online Speaking Class During Pandemic - Fierda Aulya Mantika; Johannes Ananto Prayogo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: The focus of this research is to understand how the teachers’ beliefs that the teachers have before they teaching speaking class. Moreover, the teacher will teach with a method whereas the teachers and students only using internet to connected with each other by using laptops. The data were collected by using questionnaire, observation and interview. In order to understand this research mixed method research is used to analyze the data. The result shows that teachers’ beliefs that the teachers have is in line with the actual practice in the classroom.Abstrak: Fokus dalam penelitian ini adalah mengetahui bagaimana teachers’ beliefs yang dimiliki oleh para pengajar sebelum mengajar mata kuliah berbicara. Terlebih pengajar akan mengajar dengan metode daring dimana pengajar dan siswa hanya akan terkoneksi melalui internet dan menggunakan laptop. Data dikumpulkan dengan menggunakan kuisioner, observasi dan wawancara. Untuk memahami penelitian ini, penelitian mixed method digunakan untuk menganalisa data. Hasil menunjukan bahwa teachers’ belief yang dimiliki para pengajar sesuai dengan praktek langsung di dalam kelas.